Oral Immunization of Chickens With Recombinant Lactobacillus plantarum Vaccine Against Early ALV-J Infection - Wang, Shenghua; Geng, Na; Zhou, Dong; Qu, Yi; Shi, Mengke; Xu, Yuliang; Liu, Kangping; Liu, Yongxia; Liu, Jianzhu (Frontiers in immunology, 2019)
In this study, a novel oral vaccine of recombinant ( ) containing the gp85 protein was explored, and the effects of this vaccine on the prevention of subgroup J Avian Leukosis Virus (ALV-J) infection were assessed. In the current study, the gp85 protein of ALV-J was expressed on the surface of with the surface-display motif, , by constructing a shuttle vector . Surface localization of the fusion protein was verified by western blotting and flow cytometry. Subsequently, Specific Pathogen Free Hy-Line Brown layer chickens were orally vaccinated with the recombinant and presented with high levels of serum immunoglobulin G (IgG) and secretory immunoglobulin A (sIgA) titers in bile and duodenal-mucosal fluid. After challenged with ALV-J of a 3 × 10 50% tissue culture infective dose (TCID50), serum samples of the chickens were collected and viremia was analyzed. Results showed that, compared to the and PBS control group, the recombinant group showed a significant rise in antibody levels after inoculation, and provide improved protection against ALV-J according to viremia detection. These results indicate that oral immunization with the recombinant provided an effective means for eliciting protective immune response against early ALV-J infection.